Vedic Based Faith Based Organizations (FBOs) as an Agent of Transformation for Implementing the United Nations Sustainable Development Goals (UN SDGs) - Das, Gauranga (Digital Repository of Theses, 2026)
This research examines the transformative potential of Vedic-based FBOs in supporting the implementation of the UN SDGs. Although FBOs have been acknowledged for contributing to social welfare and sustainable development across different religious backgrounds, there has been no research exploring the impact of Vedic-based FBOs on the UN SDGs. Therefore, the purpose of this study is to investigate the alignment of the UN SDGs with the Vedic-based principles guiding Vedic-based FBOs. The primary focus of this research is to assess the relationship between Vedic philosophy and sustainable development. Specifically, this research uses the case study of Govardhan Ecovillage, a Vedic-based FBO in India, to understand the relationship between Vedic philosophy and sustainable development. Qualitative methods were employed in this research using interviews with stakeholders at Govardhan Ecovillage and grounded theory. The case study explored the thematic areas such as ecological balance, community resilience, and ethical governance that enable the implementation of the UN SDGs. Additionally, this research will provide both academic and practical contributions. From an academic perspective, this study will fill a significant knowledge gap by identifying how Vedic faith traditions can support the achievement of the five Ps of the SDGs: people, planet, prosperity, peace, and partnership. From a practical perspective, this study will provide a comprehensive theoretical and methodological framework to policymakers, development professionals, and FBO practitioners to utilize Vedic philosophical principles to expedite the achievement of the 2030 Agenda. Ultimately, by demonstrating the mechanisms through which Vedic-based FBOs are able to implement sustainable practices, this study will pave the way for evidence-based collaborative efforts between faith communities and global development actors. KEYWORDS: Faith-Based Organizations, United Nations, Sustainable Development Goals, Vedas, Ramayan, Srimad Bhagavatam.